Optimized organometal halide perovskite solar cell fabrication through control of nanoparticle crystal patterning. Issue 9 (16th February 2017) - Mohamad, D. K.; Freestone, B. G.; Masters, R.; Reinhardt, M.; Canning, S.; Rodenburg, C.; Lidzey, D. G.
Abstract : The addition of hydrogen iodide to organometal halide perovskite precursor solution at 1% by volume leads to a significant enhancement in average power conversion efficiency (PCE) in inverted solar cell devices. Abstract : The addition of hydrogen iodide to organometal halide perovskite precursor solution at 1% by volume leads to a significant enhancement in average power conversion efficiency (PCE) in inverted solar cell devices, increasing from 7.7% to 11.9% and 6.1% to 10.0% in spin-cast and spray-cast devices respectively. We directly attribute this improved device performance to increased thin-film surface coverage coupled with higher optical density. X-ray diffraction studies also reveal that the HI additive facilitates full conversion of the precursor material to the crystalline perovskite phase. From solution studies, we relate these changes in device performance to the presence and distribution of precursor aggregates that effectively pattern the formation of perovskite crystals during film formation.